Anti-slip shoe covers
Patent Information
- Application Number
- JP2021075586
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-29
- Filing Date
- 2021-04-28
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2041-04-28
AI Technical Summary
【0022】 典型的な天然ポリイソプレンラテックスエマルジョン組成物は、乾燥ゴム100重量部(phr)に対して提供される。硫黄架橋剤は、0.6~1.8重量%の範囲であり;ZDECおよび/またはZDBC促進剤は、0.3~1.0重量%であり;SDBC促進剤は、0.05~0.5重量%の範囲であり;DXP促進剤は、0.2~0.8重量%の範囲であり;反応性酸化亜鉛活性化剤は、0~0.5重量%の範囲であり;カプリル酸カリウム界面活性剤は、0.1~0.5重量%の範囲であり;SDBS界面活性剤は、0.1~0.35重量%の範囲であり;ポリオキシエチレンセチル/ステアリルエーテル界面活 性剤は、0.1~0.5重量%の範囲であり;Winsgtay Lまたはp-クレゾール&ジシクロペンタジエンのブチル化反応生成物である酸化防止保存剤は、0.3~1重量%の範囲であり;水酸化アンモニウムは、0~0.36重量%の範囲である。上記に示したように、合成ポリイソプレンラテックス組成物の初期加硫組成物としては、可溶性硫黄、ZDECおよび/またはZDBC促進剤、カプリル酸カリウム界面活性剤およびSDBS界面活性剤およびポリオキシエチレンセチル/ステアリルエーテル界面活性剤が挙げられる。後加硫組成物としては、特に不溶性である硫黄、SDBC促進剤、DXP促進剤、ZDECおよび/またはZDBCが挙げられる。初期加硫組成物は、水性天然ポリイソプレンエマルジョン中の天然ポリイソプレンラテックス粒子へ硫黄の利用可能性を提供し、その後、加硫硬化サイクル中に天然ポリイソプレンの粒子全体を架橋する。後加硫組成物は、天然ポリイソプレンの粒子間領域の架橋能を提供し、それにより、高品質な実質的に一様に硬化されたポリイソプレン製品を保証する。
Smart Images

Figure 0007644481000002 
Figure 0007644481000003 
Figure 0007644481000004
Abstract
Description
[Technical field]
[0001] The present invention relates to the manufacture of natural latex shoe covers with enhanced traction and methods thereof with improved inter- and intra-particle bonding using controlled pre-vulcanized particles of natural latex dip-molded from an aqueous latex emulsion into a thin latex product. The shoe covers are made of natural rubber with a sole having an anti-slip microstructure produced by etching, and are further covered with an acrylic coating that prevents the sole from wearing rapidly. The overshoes incorporate a highly elastic natural rubber body that can be easily worn over a regular attractive shoe and prevents the attractive shoe from being exposed to moisture and mud. The natural latex used to mold the overshoe body has reduced amounts of sulfur and other accelerator crosslinking agents and is vulcanized at low temperatures of only 110°C to 130°C to provide approximately 800% elongation. [Background technology]
[0002] Natural latex shoe covers are typically made from vulcanized natural rubber due to its low cost and ease of manufacture. Natural rubber is produced in latex form by the Hevea brasiliensis tree and has unique properties. These properties make it particularly useful for the manufacture of barrier protection products. Among the unique properties of natural rubber is its high level of stereoregularity, meaning that the polymers that compose it are chains composed almost exclusively of cis-1,4-isoprene units. Furthermore, natural rubber latex is a highly branched polymer with high molecular weight and broad molecular weight distribution. These properties of the base latex result in vulcanized rubber film products with a unique combination of strength and elasticity. However, natural polyisoprene also contains proteins that have been shown to cause allergic skin reactions in some susceptible individuals.
[0003] In the dip molding process, the majority of fabricated articles containing natural polyisoprene have been focused on the development of polyisoprene gloves using the coagulant dip process. In this type of process, the glove shape former is first dipped into a solution known to destabilize the latex formulation. The coagulant layer is then dried, and the former is then dipped into a bath of compounded latex formulation. The coagulated wet latex gel is usually leached into water to remove residual surfactant, and then dried at a relatively high temperature to complete the crosslinking of the rubber film.
[0004] The use of vulcanizing or sulfur crosslinking agents in the manufacture of rubber products is well known. The effectiveness of sulfur crosslinking agents is enhanced by conventional accelerators, including dithiocarbamates, thiazoles, guanidines, thioureas, amines, disulfides, thiurams, xanthates and sulfonamides. The use of vulcanizing agents in the manufacture of polyisoprene rubber is disclosed in U.S. Patent No. 5,744,552 to D'Sidocky et al. and U.S. Patent No. 6,114,469 to Rauchfuss et al.
[0005] Stevenson, U.S. Patent No. 4,695,609, discloses a vulcanizable rubber composition containing less than 0.4 parts by weight of nitrosatable material per 100 parts by weight of rubber of xanthate polysulfide and xanthate compounds. The rubber composition contains dihydrocarbyl xanthate polysulfide and xanthate selected from hydrocarbyl xanthate metal salts and dihydrocarbyl xanthates. Aqueous latex emulsion item #9E contains sulfur, zinc oxide and zinc diethyldithiocarbamate, is stable for only 4 days, has a tensile strength at break of only 22.4 MPa, and an elongation of 830%.
[0006] Stevenson, U.S. Patent No. 5,254,635, discloses rubber compositions containing dibenzyl thiuram sulfides. Dibenzyl thiuram sulfides, such as tetrabenzyl thiuram disulfide, are compounded with dihydrocarbyl xanthogen polysulfides and / or xanthates to provide compositions that crosslink natural rubber at 120-180°C without producing harmful nitrosable materials. However, this natural latex composition does not contain sulfur and does not crosslink with the intraparticle regions of synthetic cis-1,4-polyisoprene, which has low levels of stereoregularity. Thus, the use of these crosslinkers for natural polyisoprene latex would result in a non-uniform product with inferior properties.
[0007] Munn et al., U.S. Patent No. 6,221,447, discloses rubber products and hypoallergenic rubber-like products that shrink upon application of energy. The patent describes the production of hypoallergenic rubber products that shrink from a second shape and resume their original shape and size upon application of heat. Examples include polyisoprene products that will shrink during use to fit an individual user. The curing package used to produce this product consists of agents such as peroxide and / or sulfur.
[0008] Crepeau et al., U.S. Patent No. 6,391,326, discloses stable emulsions, methods of manufacture, and applications such as forming elastomeric thin films. A stable emulsion for the production of elastomeric thin films includes (1) Phase A containing an elastomer dissolved and dispersed in a non-polar or slightly polar organic solvent, (2) Phase B containing a polymer in solution or dispersed in a polar solvent that is miscible with Phase A, and (3) a dispersing agent selected from the group consisting of block polymers and graft polymers. Droplets of Phase B having a diameter of 10 μm form in Phase A. Crepeau et al. do not teach or suggest how to stabilize polyisoprene aqueous latex emulsions against "floc" formation.
[0009] U.S. Patent No. 6,618,861 relates to a polyisoprene latex compound containing an accelerator system of 2.0 parts per million ("phr") tetramethylthiuram sulfide ("TMTD"), 0.2 phr zinc 2-mercaptobenzothiazole ("ZMBT"), 0.2 phr zinc dibutyldithiocarbamate ("ZDBC"), 0.2 phr 1,3-diphenyl-2-thiourea, and 0.2 phr zinc diethyldithiocarbamate ("ZDEC"). However, after curing, this accelerator system provides a tensile strength of only about 1,900 psi.
[0010] Dzikowicz, U.S. Patents 6,653,380 and 7,048,977, disclose latex film compounds with improved tear resistance. The method enhances the tear resistance, tensile strength, and aging properties of latex products by adding antioxidant synergists to the latex compound along with antioxidants. The latex compound includes a polymer, a stabilizing system, a film surface conditioner, and a curing system including activators, crosslinkers, and accelerators. The antioxidant synergists include 2-mercaptobenzimidazole (MBI), 2-mercaptotolumidazole (MTI), zinc 2-mercaptobenzimidazole (ZMBI), and zinc 2-mercaptotolumidazole (ZMTI). The latex product produced can be a glove, but can also include threads, balloons, and other latex-related products. The latex used with the addition of antioxidants does not prevulcanize the polyisoprene latex.
[0011] U.S. Patent No. 6,828,387 to Wang et al. discloses a polyisoprene product and method for its manufacture. The method produces a polyisoprene product that exhibits tensile strength properties similar to those of a solvent-based method using natural rubber latex. The method combines a synergistic latex with sulfur, zinc oxide, and an accelerator composition that includes dithiocarbamate, thiazole, and guanidine compounds, all three of which are present in the pre-cure stage. In a preferred embodiment, the accelerator composition includes zinc diethyldithiocarbamate (ZDEC), zinc 2-mercaptobenzothiazole (ZMBT), and diphenylguanidine (DPG) along with a stabilizer that is primarily a milk protein salt, such as sodium caseinate. The polyisoprene latex (usually 60% solids) and the stabilizer (e.g., sodium caseinate) are combined at ambient temperature (about 20-25°C). After mixing for a period of time, the mixture is diluted with water to 40% solids. Wingstay L is then added and the mixture is stirred for about 15 minutes. At this point, the pH can be adjusted to a range of about 8.5-9.0. Zinc oxide is added, followed by sulfur and accelerator compound. The elastomeric polyisoprene product produced by the method is a surgical glove dipped onto a coagulant-coated former. The aqueous latex emulsion is only minimally stable, being stable for a maximum of 8 days. The resulting surgical glove product has a tensile strength of only about 3,000 psi or 20.6 MPa. The accelerator is added to the latex emulsion, which is maintained at low temperatures for up to 8 days. The stability of this aqueous latex composition is superior to that of Stevenson (U.S. Pat. No. 4,695,609), but is still insufficient for the manufacturing process.
[0012] Dzikowicz, U.S. Patent No. 7,041,746, discloses an accelerator system for synthetic polyisoprene latex. The accelerator system includes dithiocarbamates and thioureas and is capable of producing synthetic polyisoprene thin films having tensile strengths of about 3,000 psi to about 5,000 psi at low cure temperatures. These accelerators have not been shown to initially vulcanize the polyisoprene particles, and the latex products produced have a very low modulus of 1.5 MPa at 300% elongation and tensile strengths of 20.6 to 34.4 MPa.
[0013] U.S. Patent Application Publication No. 2002 / 0173563(A1) describes a method for making dipped products from latex that involves the use of an accelerator system including zinc diethyldithiocarbamate ("ZDEC"), zinc 2-mercaptobenzothiazole ("ZMBT"), and diphenylguanidine ("DPG"). ZDEC along with ZMBT is a common accelerator system for natural rubber latex. With the addition of DPG alone, this accelerator system allows for the achievement of cured thin films having tensile strengths in excess of 3,000 psi (20 MPa).
[0014] Attrill et al., UK Patent Publication No. 2,436,566, discloses minimizing pre-vulcanization of polyisoprene latex. The method of making polyisoprene latex involves compounding synthetic polyisoprene latex with compounding ingredients and curing the latex at a low temperature to minimize pre-vulcanization. Dipping of condoms is also performed at low temperatures, typically below 15°C to 20°C. The lack of pre-vulcanization is verified by checking the strength of the rings produced, and the relaxation modulus of the pre-vulcanizate has a value of less than 0.1 MPa indicating the lack of pre-vulcanization. The latex emulsion may contain accelerators such as dithiocarbamates. The '566 patent application teaches away from pre-vulcanization of latex products prior to dipping.
[0015] US Patent Application Publication No. 2014 / 0196320 to Larson et al. discloses slip-resistant overshoes with soft cleats and methods of gripping natural surfaces. The slip-resistant overshoes include a contoured lateral strip for enhanced traction and first and second grip pads disposed inwardly of the contoured lateral strip. A web structure connects the first and second grip pads to the contoured lateral strip. A plurality of grip devices are associated with the first and second grip pads for enhanced traction on natural surfaces. The grip devices include a body, a button extending from a first end of the body, a plurality of spikes disposed around a periphery of the body, and a central spike extending from a second end of the body. The anti-slip element includes a cleat and is not formed from a natural rubber shoe cover. The waist is disposed surrounding the body between the button and the spike. The spike includes a traction arm, a plurality of ends formed along the traction arm, and a recessed surface between the first end and the second end along the traction arm. The anti-slip element includes a cleat and is not formed from a natural rubber shoe cover.
[0016] Austin's U.S. Patent Application Publication No. 2019 / 0053575 discloses an overshoe. The comfortable overshoe, which can be worn over various types of footwear, includes a soft, resilient sole and a means for removably attaching the overshoe to a boot or other footwear. The sole includes a soft, generally planar inner wall with a plurality of hollow eaves formed in and extending from an upper surface of the inner wall. A plurality of tri-radial support members extend from the bottom of the inner wall and are spaced apart to surround the bottom surface of each eaves. When a person wearing the overshoe walks across a surface having multiple irregular shapes, certain eaves and support members may be compressed, flexed, and / or stressed when the sole of the overshoe contacts the surface. This cushions the user's feet and provides a very comfortable walking experience. When an overshoe constructed as described herein comes into contact with a hard object such as gravel, depending on the size of the object and the particular portion or area of the sole that impacts with the object, the sole will conform to the object and "absorb" it or dampen the impact felt by the user. These shapes are not formed using a natural rubber coating applied to the bottom of the overshoe. Summary of the Invention [Problem to be solved by the invention]
[0017] Thus, there is a need for a high elongation elastic shoe cover made from dipping a former into a stable natural polyisoprene latex emulsion composition that provides a usable emulsion life and does not clump or flock. The composition should achieve intra- and inter-particle crosslinking in the final product. Such a composition allows for dip molding of the product in the presence of a coagulant, resulting in a product with a thinner, continuous, defect-free layer with enhanced strength and improved elasticity. Such a product will not deteriorate over time and will maintain its physical integrity. It is an object of the present invention to provide such a composition, as well as a method of making and using such a composition to dip mold slip-resistant shoe covers, and the product so made. These and other objects and advantages, as well as further features of the present invention, will become apparent from the detailed description provided herein. [Means for solving the problem]
[0018] The present invention provides a cured latex product by dipping a shoe-shaped former into an incipiently vulcanized natural latex emulsion using a calcium nitrate coagulant and curing the shoe cover so produced. The present invention relates to the manufacture of a natural latex shoe cover having enhanced traction at the ground contact portion of the shoe cover by a series of grooves and intervening ridges formed by an etching process. The etching involves an etching solution containing a non-polar solvent mixed with one or more polar solvents that dissolve the natural latex coating forming the grooves in the bottom surface of the shoe cover. The non-polar solvent is selected from toluene, benzene and other non-polar solvents that form several co-current flows due to their immiscibility with the polar solvent. Although several non-polar solvents are known, the density of the non-polar solvent is an important factor in interacting with the polar solvent to form separate flows as detailed below. The shoe cover is made of natural rubber having a sole with a slip-resistant microstructure produced by etching, which is further covered by an acrylic coating that prevents the sole from wearing rapidly. The overshoe is mixed with a highly elastic natural rubber body that can be easily worn over a commonly worn and attractive shoe that prevents the shoe from being exposed to moisture and mud. The natural latex used to form the overshoe body is resistant to sulfur and other chemicals. By reducing the amount of crosslinking agent, which is an accelerator, the initial vulcanization occurs at a low temperature of only 110°C to 130°C, providing an elongation of approximately 800%. 1. A shoe cover is manufactured by dipping a narrow former having a width of about 20% of the shoe width, first coated with a calcium nitrate coagulant coating, dried, and then dipped into natural rubber latex having only 3-4% sulfur by weight of natural rubber (phr) with a minimum of accelerators or crosslinkers with a total solids content of 50-55% at 22-25°C. The elastic stretchability of the shoe cover allows it to expand from both sides of the shoe, and the shoe cover captures the shoe worn by the user at a pressure of about 3 MPa. 2. The former is then dipped into the natural rubber coating, just the ground-contacting foot portion of the shoe, to produce a thicker latex coating on the bottom of the shoe cover. 3. The bottom portion of the former with the thicker second latex coating is then immersed in a texturing and etching bath to texture the sole of the shoe cover. The texturing bath preferably has toluene (92% by weight), ethyl alcohol (4% by weight) and acetic acid (4% by weight). Toluene is a non-polar solvent and does not interact with or dissolve polar solvents such as acetic acid, alcohol or water mixed in the second latex coating. When these three components are mixed in the etching bath, the polar solvents of ethyl alcohol and acetic acid form immiscible droplets and form a separate stream from the non-polar solvent toluene stream. When the former with the second latex coating is immersed in a gently flowing etching bath solution, it forms a parallel flow pattern of the non-polar toluene solvent with the polar ethyl alcohol and acetic acid streams. The parallel polar solvent streams dissolve the latex coating to form lines of grooves while the non-polar toluene stream forms ridges between the grooves. At the same time, the acetic acid in the polar solvent stream acts as a coagulant, coagulating and stabilizing both the grooves and the ridges between the grooves, even though the second latex layer has not yet crosslinked. The etching action of the polar solvent stream produces both the grooves and the ridges. The natural latex rubber is cured after the second latex immersion and texturing at low temperatures of about 110°C to 130°C in three adjacent heating stations of gradually increasing temperature, thereby curing the natural rubber coating. The cured latex film is highly elastic, typically having an elongation of 800%.
[0019] The latex particles in the latex emulsion used in the process are incipiently vulcanized by the incorporation of sulfur into the interstices of the latex particles. The incorporation of sulfur into natural latex particles is carried out by: 1) using a sulfur emulsion having a high content of soluble sulfur with S8 ring structure; 2) splitting or decomposing the ring structure by catalytic activity of zinc dithiocarbamate, resulting in linear sulfur in the latex emulsion for easy migration into the natural polyisoprene particles in the latex emulsion; 3) using potassium caprylate surfactant and sodium dodecylbenzene sulfonate (SDBS) surfactant to wet the polyisoprene particles in the latex emulsion, thereby making sulfur chains available for infiltration into the particles in addition to the sulfur-trapped zinc dithiocarbamate; 4) allowing sufficient time at a selected processing temperature in the range of 20°C to 30°C to gradually infiltrate the synthetic polyisoprene particles with sulfur; 5) verifying sulfur infiltration and initial vulcanization by chloroform index test, where the polyisoprene particles are no longer sticky but are in the form of dry crumbs with a chloroform index of 2.5 to 3.0. Zinc dithiocarbamate is a zinc complex of dithiocarbamate, including zinc dimethyldithiocarbamate, zinc diethyldithiocarbamate, and zinc dibutyldithiocarbamate. In addition, natural polyisoprene latex emulsion has other crosslinking agents such as sodium dibutyldithiocarbamate (SDBC), tetrabenzylthiuram disulfide, diisopropylxanthogen, tetraethylthiuram disulfide, and xanthogen sulfide to harden the interparticle regions during the vulcanization or cure cycle. Insoluble sulfur such as amorphous sulfur or polysulfur present in the sulfur added to the latex emulsion becomes soluble at the post-vulcanization cure temperature and reacts with the zinc dithiocarbamate accelerator to harden the interparticle regions during the post-vulcanization cure. The interparticle regions are cured in the initial vulcanization and the pre-vulcanized natural polyisoprene particles containing the infiltrated sulfur are also fully cured. Thus, this method of using an initial vulcanization accelerator package and a post-vulcanization accelerator package is used to produce a substantially uniform cured natural latex shoe cover film that is highly stretchable having an elongation of up to 800%.
[0020] The products thus produced have several distinguishing features that bear the imprint of this initial vulcanization method. The molecular weight between the crosslinks is lower, since the natural polyisoprene thin film of the latex is cured with improved crosslink density. The zinc complexes of dithiocarbamic acid catalytically decompose the S8 ring of sulfur, so that they can still be used as catalysts, and due to their large molecular size, do not easily penetrate the natural polyisoprene. The molecular size of zinc dibutyldithiocarbamate is larger than that of zinc diethyldithiocarbamate, which has a larger molecular size than zinc dimethyldithiocarbamate. Zinc dibenzyldithiocarbamate and zinc diphenyldithiocarbamate are even larger molecules and will resist penetration into the natural polyisoprene latex particles. Thus, the preferred zinc complexes of dithiocarbamic acid for the initial vulcanization of natural latex particles in latex emulsions are zinc dibutyldithiocarbamate (ZDBC) or zinc diethyldithiocarbamate (ZDEC). There is an accumulation of zinc-containing compounds surrounding each of the original natural polyisoprene particles, and this microstructural feature can be readily observed by microprobe elemental analysis using an electron microscope. The natural polyisoprene films produced typically have acceptable tensile strength, acceptable tensile modulus, and elongation to break at crack faces passing through both the interparticle and intraparticle regions, indicating that the intraparticle and interparticle regions are of substantially equal strength within the natural latex films produced.
[0021] The method for making a natural polyisoprene shoe cover includes the use of a natural latex emulsion, which is an initial vulcanization composition. Preferably, the natural polyisoprene particles are cis-1,4-polyisoprene, have a diameter in the range of about 0.2 to 2 micrometers, and are maintained in the aqueous medium of the latex emulsion. The initial vulcanization composition typically has sulfur with a high content of soluble sulfur from S8 ring structures broken down by a zinc dithiocarbamate accelerator, which breaks down the S8 sulfur ring structures. A combination of surfactants including potassium caprylate, also known as the potassium salt of octanoic acid, and sodium dodecylbenzene sulfonate (SDBS) is used to deliver the broken down sulfur molecules to the latex. The initial vulcanization of the natural latex particles in the natural latex emulsion occurs over a period of 9 hours to 2 days depending on the temperature of the latex emulsion, which generally ranges from 20°C to 30°C. The degree of initial vulcanization of natural latex particles is monitored by the chloroform index test, where the latex particles progress from tacky (index 1) to less tacky (index 3) when the initial vulcanization sulfur is incorporated within the particles. The post-vulcanization composition may contain amorphous sulfur or polysulfur that is insoluble at the latex emulsion temperature but soluble at the vulcanization or cure temperature. Other accelerators in synthetic aqueous latex emulsions include, but are not limited to, zinc diethyldithiocarbamate (ZDEC), sodium diethyldithiocarbamate (SDEC), sodium dibutyldithiocarbamate (SDBC) and diisopropyl xanthogen polysulfide (DXP). Zinc oxide may be added as an activator.
[0022] A typical natural polyisoprene latex emulsion composition is provided per 100 parts by weight (phr) of dry rubber: sulfur crosslinker in the range of 0.6-1.8 wt%; ZDEC and / or ZDBC accelerator in the range of 0.3-1.0 wt%; SDBC accelerator in the range of 0.05-0.5 wt%; DXP accelerator in the range of 0.2-0.8 wt%; reactive zinc oxide activator in the range of 0-0.5 wt%; potassium caprylate surfactant in the range of 0.1-0.5 wt%; SDBS surfactant in the range of 0.1-0.35 wt%; polyoxyethylene cetyl / stearyl ether surfactant in the range of 0.05-0.5 wt%; The preservative, Winsgtay L or butylated reaction product of p-cresol & dicyclopentadiene, is in the range of 0.3-1 wt%; and ammonium hydroxide is in the range of 0-0.36 wt%. As indicated above, the initial vulcanization composition of the synthetic polyisoprene latex composition includes soluble sulfur, ZDEC and / or ZDBC accelerators, potassium caprylate surfactant and SDBS surfactant and polyoxyethylene cetyl / stearyl ether surfactant. The post-vulcanization composition includes sulfur, SDBC accelerator, DXP accelerator, ZDEC and / or ZDBC, which are particularly insoluble. The initial vulcanization composition provides sulfur availability to the natural polyisoprene latex particles in the aqueous natural polyisoprene emulsion, which then crosslinks the entire particles of natural polyisoprene during the vulcanization cure cycle. The post-vulcanization composition provides the ability to crosslink the interparticle regions of the natural polyisoprene, thereby ensuring a high quality, substantially uniformly cured polyisoprene product. [Brief description of the drawings]
[0023] [Figure 1]Figures 1a and 1b show two views of the formers used to manufacture shoe covers according to the present invention. Figure 1a shows a narrow and thin aluminum alloy former with a width of only about 3mm to 8mm, and the manufactured shoe cover stretches to elastically capture the shoe and secure the shoe cover to the shoe when it shrinks. Figure 1b shows another view of the aluminum alloy former showing the area where the shoe cover former is inserted into the latex bath. [Diagram 2] Illustrates the tensile strength vs. elongation properties of natural latex rubber as disclosed in U.S. Patent No. 6,673,871. The natural rubber film exhibits the lowest tensile stress and highest elongation. Clearly, the natural rubber film is best suited for shoe covers as it exerts low loads on the shoe while still gripping the shoe worn by the user. [Diagram 3]Illustrates a flow chart of the manufacturing method of shoe covers. The former is first stripped of the previously manufactured shoe cover, washed with an acid cleaner, coated with calcium nitrate coagulant, and dried in an oven. The coagulant-coated former is dipped into natural rubber latex #1 with reduced amounts of sulfur and minimal amounts of accelerator. The coagulant coating destabilizes the latex and forms a thin film of natural rubber film on the former. The ground contacting the bottom of the shoe cover is then dipped into a denser natural rubber latex to form a thicker coating on the bottom of the shoe cover. This thicker coating prevents tearing at the bottom when the shoe cover is worn. The thicker shoe cover bottom is then dipped into a texturing bath with an approximately linear flow of liquid contained therein. The bath contains 92% by weight toluene, 4% by weight acetic acid, and 4% by weight ethyl alcohol, which form separate streams due to their immiscibility with toluene. The ethyl alcohol and acetic acid extract water from the thicker coating of natural rubber and dissolve the natural rubber latex, forming grooves. At the same time, the acetic acid, which is a destabilizer for natural latex emulsions, coagulates and stabilizes the latex coating, preventing further dissolution. The toluene stream does not attack the natural rubber latex coating, forming ridges in the coating. When a person wearing the shoe cover walks and increases friction, the ridges and grooves direct any water, oil or grease present on the ground to the rear of the shoe cover. The bottom of the shoe cover is then coated with an acrylic polymer coating to enhance wear properties. The shoe cover with multiple coatings is then heated in three successive ovens, maintained at 110°C, 120°C and 130°C, to cure the natural rubber and polymer coatings and produce a one-piece, easy-to-wear shoe cover. [Figure 4] 1 is a photograph of ridges and grooves formed on the floor contact surface of the bottom of a shoe cover. [Diagram 5] 1 illustrates the etching microstructure of grooves and ridges formed on the bottom floor contact surface of the shoe cover. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The present invention is based on the discovery that soluble sulfur, such as the S8 ring of sulfur, catalyzed by a zinc complex of dithiocarbamic acid in combination with potassium caprylate and sodium dodecylbenzene sulfonate (SDBS) surfactants produces early vulcanized natural polyisoprene particles in a latex composition. This latex composition allows for the production of latex film products by dipping a coagulant-coated or coagulant-free dipping former into the composition. The surfactant package inhibits natural polyisoprene particle agglomeration and flocculation. The latex dipping film has natural polyisoprene particles that are crosslinked, with the interparticle regions crosslinked during vulcanization cure to produce both intraparticle and interparticle crosslinks. The resulting product contains a high quality and uniform latex film.
[0025] The latex stabilizing composition is one that keeps the particles of natural polyisoprene separated from each other in an aqueous medium. Since the polyisoprene particles do not contact each other, the polyisoprene particles cannot form agglomerates or flocs. This is important because once the particles start to form agglomerates, they may never separate due to van der Waals forces. Preferably, the latex stabilizing composition includes a surfactant package that includes at least one surfactant. Anionic surfactants are preferred, and those that can remain stable for periods well in excess of one month, and up to two months or more, are especially preferred. An example of such a surfactant is sodium dodecylbenzene sulfonate (SDBS). Other examples include, but are not limited to, other alkylaryl sulfonates, alkyl sulfonates (e.g., C14 olefin sulfonate, sold under the trade name Calsoft AOS-40 (Pilot Chem. Co., Red Bank, NJ)), olefin sulfonates, and alcohol sulfonates (e.g., sodium lauryl sulfonate). The SDBS or another alkylaryl sulfonate is preferably present in an amount of about 0.1-0.35% by weight based on the dry weight of the polyisoprene. The SDBS or another alkylaryl sulfonate can be combined with one or more other surfactants, such as potassium caprylate, polyoxyethylene cetyl / stearyl ether, and the like. For example, the SDBS or another alkylaryl sulfonate can be combined with potassium caprylate, alone or further combined with polyoxyethylene cetyl / stearyl ether. When the SDBS or another alkylaryl sulfonate is used in combination with one or more other surfactants, each surfactant is preferably present in an amount of about 0.05-1.2% by weight based on the dry weight of the polyisoprene, with the total amount of the surfactant package being about 0.4-1.2% by weight based on the dry weight of the polyisoprene.When SDBS or another alkylaryl sulfonate is used in combination with potassium caprylate and polyoxyethylene cetyl / stearyl ether, preferably the polyoxyethylene cetyl / stearyl ether is present in an amount of about 0.1 to 0.5% by weight, based on the dry weight of polyisoprene.
[0026] In view of the above, the present invention provides a surfactant-stabilized pre-vulcanized natural polyisoprene latex composition having a chloroform index of 3.0. The chloroform index test measures the degree of pre-vulcanization of natural latex particles in an aqueous latex emulsion by combining equal volumes of latex and chloroform at room temperature and allowing the mixture to stand for 3 minutes. The chloroform coagulates the latex and the resulting softness is numerically graded. The softness of the coagulum indicates the degree of pre-vulcanization of the latex. The more pre-vulcanized the latex is, the more the coagulum loses its thickness and becomes more brittle. A rating of 2.5 indicates that small lumps have formed, a rating of 3.0 indicates that the lumps are not sticky, a rating of 3.5 indicates that the lumps are not only not sticky but also easily crumble, and a rating of 4.0 indicates that dry lumps have formed, evidence of a high degree of pre-vulcanization of the natural latex particles. The pre-vulcanization is monitored to ensure that the natural latex emulsion is ready for immersion at any time.
[0027] The pre-vulcanization composition contains potassium caprylate and SDBS or another alkylaryl sulfonate surfactant along with zinc dithiocarbamate and soluble sulfur. The latex emulsion along with the surfactant wets the natural polyisoprene particles, and the catalytic action of the zinc dithiocarbamate breaks the rings of the soluble S8 molecules to form linear chains of soluble sulfur pre-vulcanized particles of synthetic polyisoprene. The post-vulcanization composition has sulfur and other accelerators that cause inter-particle crosslinking during the vulcanization cure. Such crosslinking results in a more uniform latex film with greater strength and elongation properties and crosslink density.
[0028] Sulfur is preferably present in the natural polyisoprene latex emulsion in an amount of about 0.8-1.8% by weight based on the dry weight of polyisoprene. When zinc oxide is used, it is preferably present in an amount of about 0-0.5% by weight based on the dry weight of polyisoprene, while when zinc diethyldithiocarbamate or zinc dibutyldithiocarbamate is used, it is preferably present in an amount of about 0.3-1.0% by weight or more preferably about 0.3-0.45% by weight based on the dry weight of polyisoprene.
[0029] Examples of suitable wetting agents include, but are not limited to, salts of fatty acids (e.g., sodium or potassium salts) that are anionic, such as sodium stearate, sodium oleate, and potassium caprylate. Potassium caprylate is advantageously used with salts of short chain fatty acids, SDBS, and polyoxyethylene cetyl / stearyl ether. Potassium caprylate is used in an amount of about 0.1-0.5% by weight based on the dry weight of polyisoprene.
[0030] The penetration of the initial vulcanization composition components into the polyisoprene particles is a strong function of the polyisoprene particle size and particle size distribution. Smaller particles usually have a larger surface area, and the initial vulcanization composition components will penetrate these small particles more quickly. However, these smaller particles tend to initial vulcanize faster than larger particles, and their larger surface area results in a larger intraparticle region. Larger particles may be agglomerates of smaller particles and are less likely to initial vulcanize. Larger particles have a smaller surface area, and the initial vulcanization composition components will penetrate these larger particles more slowly. The smaller surface area results in a smaller intraparticle region. Thus, there is a delicate balance when selecting the size and size range distribution of natural polyisoprene particles to obtain optimal strength properties that balance initial vulcanization intraparticle crosslinking and post vulcanization interparticle crosslinking. As shown above, particles in the range of about 0.2 to 2 micrometers provide optimal results. The penetration of the components of the initial vulcanization composition into the natural polyisoprene particles is a function of the diffusion process itself, a linear function of time, and an exponential function of temperature, reflecting a heat-activated process. Thus, an increase in temperature of a few degrees during the initial vulcanization step significantly increases the rate of initial vulcanization. For example, initial vulcanization at room temperature takes about 3-5 days, or even up to about 9 days, while initial vulcanization at higher temperatures, e.g., about 50-70°C, takes only about 3-7 hours. However, more rapid precure is usually avoided in order to avoid initial vulcanization occurring only around large agglomerates, which would result in poor ultimate strength properties of the thin film: this is a surface cure reaction, and the use of potassium caprylate has been demonstrated to promote the migration of the curative into the particles, accelerating the rate of initial vulcanization.
[0031] Preferably, the post-vulcanization composition includes sodium dibutyldithiocarbamate (SDBC), sulfur, a thiuram compound, and / or a xanthogen compound, alone or in further combination with a surfactant. Examples of suitable xanthogens include, but are not limited to, diisopropyl xanthogen polysulfide (DXP), diisopropyl xanthogen, tetraethyl thiuram disulfide, and xanthogen sulfide. DXP is the preferred xanthogen. When present, the xanthogen is present in an amount of about 0.05 to 0.5% by weight, based on the dry weight of the polyisoprene. An example of a thiuram compound is tetrabenzyl thiuram disulfide. When present, tetrabenzyl thiuram di The sulfide is present in an amount of about 0.1-0.75% by weight based on the dry weight of polyisoprene. The post-vulcanization composition is one which upon activation at elevated temperatures (e.g., 110-130°C) induces interparticle crosslinking. In addition, this post-vulcanization cure also cures the crosslinks between the natural polyisoprene particles and the infiltrated sulfur. Such crosslinking results in a more uniform latex film with greater strength and elongation properties.
[0032] The method includes adding a latex stabilizing composition, such as one that includes a surfactant package including at least one surfactant, such as at least one surfactant selected from the group consisting of alkylaryl sulfonates (e.g., SDBS), alkyl sulfonates (e.g., olefin sulfonates), and alcohol sulfonates (e.g., sodium lauryl sulfonate). When SDBS is present, it is preferably present in an amount of about 0.1 to 0.35% by weight, based on the dry weight of the polyisoprene. SDBS can be combined with potassium caprylate, either alone or together with polyoxyethylene cetyl / stearyl ether. A preferred surfactant package includes SDBS, potassium caprylate, and polyoxyethylene cetyl / stearyl ether. When polyoxyethylene cetyl / stearyl ether is present, it is preferably present in an amount of about 0.1 to 0.5% by weight, based on the dry weight of the polyisoprene. Upon addition of the latex stabilizing composition, the emulsion is stirred, for example, for about one day, to keep the polyisoprene particles from contacting each other.
[0033] The method then includes the steps of adding an incipient vulcanizing composition to compound the natural polyisoprene latex emulsion: (a) a zinc dithiocarbamate selected from zinc diethyldithiocarbamate and zinc dibutyldithiocarbamate and combinations thereof; (b) sulfur, preferably with a high S8 content; and (c) a wetting agent. The wetting agent is preferably a fatty acid salt, such as sodium stearate, sodium oleate, or potassium caprylate. The aqueous latex emulsion is stirred at about 20-25°C for about 3-4 days or at about 50-70°C for about 3-7 hours, and periodically inspected for penetration of the incipient vulcanizing agent into the synthetic polyisoprene particles by using an isopropanol index test. The reason for applying this sequence is that polyisoprene latex has an inherent tendency to flock and "surface harden" due to peripheral reactions with sulfur catalyzed by ZDBC or ZDEC. This must be prevented to avoid tightly bound particles. The presence of surfactants and the generation of cleaved S8 chains of sulfur allow diffusion of sulfur into the particles.
[0034] The method further includes adding the post-vulcanization composition to the natural polyisoprene latex emulsion along with an accelerator selected from the group consisting of SDBC, reactive zinc oxide, thiurams and xanthogens, such as sodium diethyldithiocarbamate, sodium dibutyldithiocarbamate, tetrabenzylthiuram disulfide. When present, the reactive zinc oxide is preferably present in an amount of about 0-0.5% by weight based on the dry weight of the polyisoprene. The thiuram may be tetraethylthiuram disulfide, tetrabenzylthiuram disulfide, and when present, is preferably present in an amount of about 0.75% by weight or less based on the dry weight of the polyisoprene. The xanthogen may be DXP, diisopropylxanthogen, or xanthogen sulfide. When present, the xanthogen is preferably present in an amount of about 0.2-0.8% by weight based on the dry weight of the polyisoprene. The composition thus produced is stable for up to about 60 days at 25° C. and can be used on the manufacturing line. EXAMPLES
[0035] Table 1 below shows examples of compositions that exhibit early cure behavior.
[0036] [Table 1]
[0037] Thus, the present invention further provides a method for producing a natural polyisoprene latex product. The former can be any suitable former known in the art. The composition of the present invention is particularly useful for layering on a former for a shoe cover. The method comprises immersing a coagulant-coated former into the above pre-vulcanized natural polyisoprene aqueous latex emulsion composition having a solids content of 50-55% and a viscosity of 18-22 seconds using Ford Cup #4 to form a thin film of latex film having a thickness of 200-350 microns comprising individual particles of pre-vulcanized natural polyisoprene in contact with each other on the surface of the former.
[0038] After the first layer of latex film is not low in viscosity and has a typical thickness of 200-350 microns, the bottom of the shoe cover is dipped into a denser natural polyisoprene emulsion having 50-55% solids and a viscosity of 25-30 seconds using Ford cup #6 to form a thicker latex layer of about 800-1200 microns at the bottom of the shoe cover. This enhanced thickness of the latex layer at the bottom prevents tearing when the shoe cover is donned. The method further includes etching the thicker layer of natural latex with an etching solution of toluene, ethyl alcohol, and acetic acid, which forms three separate streams due to the immiscibility of toluene with ethyl alcohol and acetic acid. After this, the entire shoe cover is dipped into the polymer solution. The natural rubber film is post-vulcanized by heating the film, for example, to about 110-130°C for about 8-15 minutes. During this time, the interparticle regions are crosslinked. The intraparticle regions also further crosslink, producing a more uniform latex product.The method then includes peeling the latex film from the former.
[0039] Figure 1 shows the former used to make the shoe covers in two views: Figure 1a and Figure 1b. Figure 1a is a side view of the former and Figure 1b is a front view of the former. The former is about 20% of the width of the shoe cover when worn. The shoe cover must extend to cover the shoe worn by the user.
[0040] Figure 2 shows the load versus elongation for natural latex rubber and nitrile rubber. Clearly, natural latex has the longest elongation before break with an elongation of 800%. This also applies to the lowest load for shoes worn by users due to its low modulus.
[0041] FIG. 3 illustrates a process flow diagram for manufacturing a shoe cover. The process begins with stripping the coated shoe cover. The former is dipped into a nitric acid bath, then into two acid baths, then into a calcium nitrate coagulant bath. The former is then dried in an oven to form a dry coagulant coating. It is then dipped into natural rubber latex #1 having about 50-55% total solids at 20-25°C. The viscosity of the latex is about 18-22 seconds using a Ford cup #4. The thickness of the latex layer formed is about 200-350 microns. The latex layer coated former is dipped into a pre-leach bath. The latex coated former is then dipped into a second latex bath having 50-55% solids and about 25-30 seconds using a Ford cup #6 to a depth that will create the ground contact portion of the shoe cover. The second latex dip creates a thicker layer of natural latex layer, usually 800-1200 microns. The thicker layer at the bottom of the shoe cover is etched in a texturing bath, which has a slow-flowing solution of toluene, ethyl alcohol and acetic acid, forming a separate stream due to the immiscibility of toluene, ethyl alcohol and acetic acid. The ethyl alcohol and acetic acid streams etch the second thicker coating of natural latex to create grooves. The toluene does not attack the latex layer, forming ridges that join the grooves formed by the etching action of the alcohol and acetic acid. The etched second latex layer is then pre-leached in two baths and then immersed in a polymer coating bath, which upon curing will protect the second latex layer at the bottom of the shoe cover from abrasion. The coated shoe cover is passed through three ovens at temperatures of 110°C, 120°C and 130°C in sequence. Due to the low temperature curing of the natural latex layer, the elastic modulus of the latex layer is low and the stretchability of the latex is over 800%, allowing it to stretch and capture the shoes worn by the user without applying a large amount of load to the shoes.
[0042] FIG. 4 is a photograph of the bottom half of a shoe cover. At the top of the figure, there are nearly parallel ridges around the perimeter of the grooves. The ridges are spaced approximately 5 mm apart from the grooves between them. The half-width of the shoe cover with the nearly parallel ridges is approximately 60 mm. The grooves combined with the ridges serve to direct oil or water to the rear of the shoe as the shoe cover, when worn, is raised and walked upon in a forward motion.
[0043] Figure 5 is an optical micrograph of the grooves and ridges at approximately 40x. The figure shows two ridges with a groove between them. The tops of the ridges appear linear.
[0044] All references mentioned in this specification, including publications, patent applications, and patents, are incorporated by reference into this specification to the same extent as if each reference was individually and specifically indicated to be incorporated by reference and was set forth in its entirety herein.
[0045] In the context of describing the present invention (particularly in the context of the claims that follow), the use of the terms "a," "an," "the," and similar expressions shall be construed to encompass both the singular and the plural, unless otherwise indicated herein or clearly contradicted by context. The recitation of ranges of values herein, unless otherwise indicated herein, is merely intended to serve as a shorthand method of expressing each separate value falling within the range individually, and each separate value is incorporated herein as if it were individually set forth herein. All methods described herein may be performed in any suitable order, unless otherwise indicated herein or clearly contradicted by context. The use of any and all examples or exemplary language (e.g., "such as") provided herein is merely for the purpose of better illustrating the present specification and is not intended to limit the scope of the present invention unless otherwise claimed. No language herein should be construed as indicating any non-claimed element essential to the practice of the invention.
Claims
1. 1. A natural polyisoprene latex shoe cover product comprising: a. natural polyisoprene particles comprised of cis-1,4-isoprene units that have been catalytically broken down into sulfur chains by an accelerator and initially vulcanized by the addition of soluble sulfur that has been incorporated into the natural latex particles by the use of one or more surfactants; b. the natural polyisoprene particles are incipiently vulcanized by the addition of soluble sulfur chains produced by the addition of an accelerator; c) the sulfur chains are incorporated into natural latex particles by the addition of at least one surfactant, thus forming a modified natural polyisoprene that is used to form the natural polyisoprene latex shoe cover product; The shoe cover product comprises: d. a first layer formed from the modified natural polyisoprene and a coagulant applied onto a shoe cover former; e. a second layer formed of unmodified natural rubber latex having a higher viscosity than the modified natural polyisoprene applied over the modified natural polyisoprene of the first layer of d; f. the second layer of e is etched to include parallel grooves and ridges surrounding the grooves; g. the shoe cover former having the second layer etched onto the first layer is immersed in a polymer solution and cured by passing through three ovens set at 110° C., 120° C. and 130° C.; Natural polyisoprene latex shoe cover products.
2. 10. The natural polyisoprene latex shoe cover product of claim 1, wherein said first layer of said modified natural polyisoprene is 200-350 microns thick.
3. 10. The natural polyisoprene latex shoe cover product of claim 1, wherein said second layer is 800 to 1200 microns thick.
4. 1. A method for making a natural polyisoprene latex shoe cover product, the method comprising: a. Natural polyisoprene particles are prepared by the addition of soluble sulfur, which is catalytically broken down into sulfur chains by an accelerator and incorporated into the natural latex particles by the use of one or more surfactants. and subjecting the mixture to initial vulcanization; b. immersing the coagulant-coated shoe cover former in a natural latex bath containing said pre-vulcanized natural polyisoprene particles, thereby forming a first natural latex layer; c) immersing the former with the first natural latex layer coated thereon in a natural latex having a higher viscosity than the natural latex containing the initially vulcanized natural polyisoprene particles to form a second natural latex layer thicker than the first natural latex layer; d) etching the second natural latex layer in separate co-current laminar flows of a non-polar solvent and a polar solvent, the polar solvent dissolving the second natural latex layer to form parallel grooves and the non-polar solvent sparing the second natural latex layer to form ridges surrounding the grooves; e. immersing the former having the second natural latex layer etched onto the first natural latex layer into a polymer solution; f. passing the polymer solution soaked former with the first and second natural latex layers through three ovens set at 110° C., 120° C. and 130° C. to cure the first natural latex layer, the second natural latex layer and the polymer solution polymer coating; A method comprising:
5. The soluble sulfur is a high level of S 8 The method of claim 4, which comprises a sulfur ring.
6. 6. The process of claim 4 or 5, wherein the accelerator is selected from the group consisting of zinc diethyldithiocarbamate (ZDEC) or zinc dibutyldithiocarbamate (ZDBC) and combinations thereof.
7. The method according to any one of claims 4 to 6, wherein the surfactant comprises potassium caprylate, polyoxyethylene cetyl / stearyl ether, alkylaryl sulfonate, alkyl sulfonate, olefin sulfonate, alcohol sulfonate and / or combinations thereof.
8. The method of claim 7, wherein the alkylaryl sulfonate is sodium dodecylbenzene sulfonate (SDBS).
9. The process according to claim 7, wherein the alkyl sulfonate is an olefin sulfonate.
10. The method according to claim 7, wherein the alcohol sulfonate is sodium lauryl sulfonate.
11. The method according to any one of claims 4 to 10, wherein the non-polar solvent is toluene.
12. The method according to any one of claims 4 to 10, wherein the non-polar solvent is benzene.
13. The method according to any one of claims 4 to 12, wherein the polar solvent is ethyl alcohol.
14. The method according to any one of claims 4 to 12, wherein the polar solvent is acetic acid.
Citation Information
Patent Citations
Rubber latex made auto - tube - tool - server
JP1982146502U
Immersion-molded synthetic polyisoprene latex articles with improved intraparticle and interparticle crosslinking.
JP2011519606A